New formats of convergencies of higher education: research in binational cities of the southern Cone of Latin America - Viera-Duarte, Patricia (Universidade Estadual de Campinas, 2018)
This article shows the of a study about policies of democratisation and internationalisation of Higher Education in border cities linked of Brazil, Argentina and Uruguay; more precisely “binational cities” where there is evidence of international and subnational logics in the treatment of problems related to accessand performance in that level. This research is framed in a programme of Posdoctoral Studies, and its objectives are: describing policies of democratisation of Higher Education in frontier regions of South America; comparing discourses of national educational politic (and bilateral agreements) with the interpretation of local actors in border contexts; providing material to the methodological reflection about researches regarding education, internationalisation, democratisation and citizenship in contexts of frontier. In that order, the analysis of official documents, interviews and focus groups to actors involved in experiences of Higher Education in the border cities as have been used. The first findings of the research are presented in this article.